Effect of milk serum proteins on aggregation, bacteriostatic activity and digestion of lactoferrin after heat treatment. (1st February 2021) - Xiong, Ling; Boeren, Sjef; Vervoort, Jacques; Hettinga, Kasper
Highlights: Whey proteins accelerate lactoferrin aggregation through disulphide interchange. Lactoferrin and β-lactoglobulin influence each other's response to heat treatment. Bacteriostatic activity of lactoferrin declines after milk protein aggregation. Lactoferrin/whey aggregates formed at 75 °C resist infant in vitro digestion. Abstract: To establish the effect of the presence of milk serum proteins on heat-induced changes to lactoferrin, lactoferrin alone, and lactoferrin mixed with either milk serum or β-lactoglobulin was heated at 65 °C, 70 °C and 75 °C for 30 min. After heating, the effect of milk serum proteins on aggregation of lactoferrin was characterized, after which the effect of such aggregation on digestion and bacteriostatic capacity of lactoferrin were determined. The presence of milk serum proteins accelerated the aggregation of lactoferrin during heating through thiol/disulphide interchange. Lactoferrin also formed disulphide-linked aggregates when it was heated with β-lactoglobulin. Protein aggregates formed at 75 °C were much more resistant to infant digestion, causing decreased peptide release from lactoferrin. Heating lactoferrin and milk serum proteins together accelerated the loss of bacteriostatic activity upon heating. In conclusion, heat-induced aggregation of lactoferrin with milk serum proteins affected both its digestion and its bacteriostatic activity.